Technoeconomic Analysis and Optimization of Hybrid Solar-Wind-Hydrodiesel Renewable Energy Systems Using Two Dispatch Strategies - Tiansheng Chen; Minglei Wang; Reza Babaei; Mohammad Esmaeili Safa; Ali Asghar Shojaei (International Journal of Photoenergy, 2023)
Sustainable generation is impacted by the adoption of renewable energy, the growth of energy markets, and economic strategies. This paper offers a sustainable strategy and a technoeconomic analysis of off-grid hybrid energy systems (HES) in remote islands of Iran, including Lavan, Larak, and Failaka, utilizing PV module, wind turbine, and hydrokinetic turbines. Hourly wind speed, solar irradiation, and hydrovelocity have been implemented under load following (LF) and cycle charging (CC) dispatch strategies in order to ascertain the most appropriate systems. Lavan Island achieves the winning HES with a CC dispatch strategy, which consists of 3 hydroelectric turbines, 1 wind turbine, 349 kW of solar power, 150 kW of generator power, 316 kWh of batteries, and 287 kW of the converter. This ideal HES, which generates a consistent generation profile and reasonable net present cost (NPC) and cost of energy (COE) of M0.160$ and $0.013 kWh, respectively, can be practically attained in these areas. LF-controlled optimal solutions use less fuel than CC-based ones, leading to a higher share of renewable energy. Compared to Larak and Lavan, the CC- and LF-controlled options on Failaka Island generate cleaner electricity with emissions that are 57% and 44% lower. Regarding the ability to recoup the project’s initial investment costs, long-term energy production would be more financially viable than short-term. Short-term projects with higher financial uncertainty due to the salvage cost should use the CC method.